PENGARUH METODE INQUIRI TERHADAP LITERASI SAINS DAN HASIL BELAJAR IPA SISWA KELAS V SDN 4 SANGSIT - handayani, Ni Nyoman lisna; Muliastrini, Ni Ketut Erna (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2021)
This research aims to investigate the effect of inquiry model implementation towards science literacy and science learning outcome of SDN 4 Sangsit. This was quasi-experimental research with Posttest-Only Control-Group Design. Research population was all students V SD 4 Sangsit which consisted of 40 students. A total of 40 students were selected as the sample which was determined by random sampling technique. Science literacy data were collected using questionniare and science learning outcome data were collected using multiple choice test. Data were analyzed using MANOVA (Multivariate Analysis of Variance) assisted by SPSS 17.00 for windows. Research results show: First, science literacy of students who followed inquiry method was better than students who followed conventional learning. Second, science learning outcome of students who followed inquiry method was better than students who followed conventional learning. Third, science literacy and learning outcome of students who followed inquiry method were significantly better than students who followed conventional learning.